STRATEGI KELOMPOK SADAR WISATA DALAM MENINGKATKAN KUNJUNGAN WISATAWAN PADA OBJEK WISATA HIU PAUS KABUPATEN SUMBAWA - Rahayu, Sri; Sumbawati, Novi Kadewi; Evinnata, Dias (Jurnal Ekonomi & Bisnis, 2024)
This study aims to analyze the strategies of tourism awareness groups (Pokdarwis) in increasing foreign tourist visits to the whale shark tourist attraction in Sumbawa District. The type of this study was descriptive with a qualitative approach. The type of data used in this study was qualitative obtained directly from primary sources. The qualitative data used was collected using research instruments in the form of interview guides. The data sources who became research informants were 16 people consisting of key informants and main informants. The data that has been collected was analyzed descriptively by adopting the SWOT analysis model to examine internal and external factors at the whale shark tourist attraction in Sumbawa District. The results of this study indicate that the intersection of internal factors and external factors for the strategies of Pokdarwis in managing the whale shark tourist attraction in Sumbawa District was in quadrant I. The strategy that can be implemented in this condition was to support aggressive policies (growth oriented strategy). Pokdarwis must support aggressive policies so that the appropriate strategy is the S-O strategy, namely implementing it by utilizing the strengths and opportunities it has to overcome the weaknesses and threats faced so that it can increase foreign tourist visits to the whale shark tourist attraction in Sumbawa District. In addition, through the SWOT matrix four alternative strategies were produced to increase foreign tourist visits to the whale shark tourist attraction in Sumbawa District, namely the S-O strategy, S-T strategy, W-O strategy, and W-T strategy.